Strategies to overcome/penetrate the BBB for systemic nanoparticle delivery to the brain/brain tumor - Liu, Hai-Jun; Xu, Peisheng (Advanced drug delivery reviews, 2022)
[Display omitted] Despite its prevalence in the management of peripheral tumors, compared to surgery and radiation therapy, chemotherapy is still a suboptimal intervention in fighting against brain cancer and cancer brain metastases. This discrepancy is mainly derived from the complicatedly physiological characteristic of intracranial tumors, including the presence of blood–brain barrier (BBB) and limited enhanced permeability and retention (EPR) effect attributed to blood–brain tumor barrier (BBTB), which largely lead to insufficient therapeutics penetrating to tumor lesions to produce pharmacological effects. Therefore, dependable methodologies that can boost the efficacy of chemotherapy for brain tumors are urgently needed. Recently, nanomedicines have shown great therapeutic potential in brain tumors by employing various transcellular strategies, paracellular strategies, and their hybrids, such as adsorptive-mediated transcytosis, receptor-mediated transcytosis, BBB disruption technology, and so on. It is compulsory to comprehensively summarize these practices to shed light on future directions in developing therapeutic regimens for brain tumors. In this review, the biological and pathological characteristics of brain tumors, including BBB and BBTB, are illustrated. After that, the emerging delivery strategies for brain tumor management are summarized into different classifications and supported with detailed examples. Finally, the potential challenges and prospects for developing and clinical application of brain tumor-oriented nanomedicine are discussed.